Surprising production of a new urdamycin derivative by S. fradiae ΔurdQ/R - Fedoryshyn, M. (2007)
A strain (S. fradiae ΔurdQ/R) with mutations in urdQ and urdR encoding a dTDP-hexose-3,4-dehydratase and a dTDP-hexose-4-ketoreductase, respectively, produces a new urdamycin analogue (urdamycin X) with changes in the polyketide structure. The structure of urdamycin X has been elucidated by NMR spectroscopy. Urdamycin X was not detectable, even in small amounts, in either S. fradiae ΔurdQ, in S. fradiae ΔurdR or in S. fradiae A0, a mutant lacking all glycosyltransferase genes. Complementation of S. fradiae ΔurdQ/R restored urdamycin A production indicating that the mutations did not cause any polar effect.